Serum levels of pancreatic stone protein (PSP)/reg1A as an indicator of beta-cell apoptosis suggest an increased apoptosis rate in hepatocyte nuclear factor 1 alpha (HNF1A-MODY) carriers from the third decade of life onward - Bacon, Siobhan (BioMed Central, 2012)
BACKGROUND: Mutations in the transcription factor hepatocyte nuclear factor-1-alpha (HNF1A) result in the commonest type of maturity onset diabetes of the young (MODY). HNF1A-MODY carriers have reduced pancreatic beta cell mass, partially due to an increased rate of apoptosis. To date, it has not been possible to determine when apoptosis is occurring in HNF1A-MODY.We have recently demonstrated that beta cell apoptosis stimulates the expression of the pancreatic stone protein/regenerating (PSP/reg) gene in surviving neighbour cells, and that PSP/reg1A protein is subsequently secreted from these cells. The objective of this study was to determine whether serum levels of PSP/reg1A are elevated during disease progression in HNF1A-MODY carriers, and whether it may provide information regarding the onset of beta-cell apoptosis. METHODS: We analysed serum PSP/reg1A levels and correlated with clinical and biochemical parameters in subjects with HNF1A-MODY, glucokinase (GCK-MODY), and type 1 diabetes mellitus. A control group of normoglycaemic subjects was also analysed. RESULTS: PSP/reg1A serum levels were significantly elevated in HNF1A-MODY (n = 37) subjects compared to controls (n = 60) (median = 12.50 ng/ml, IQR = 10.61-17.87 ng/ml versus median = 10.72 ng/ml, IQR = 8.94-12.54 ng/ml, p = 0.0008). PSP/reg1A correlated negatively with insulin levels during OGTT, (rho = −0.40, p = 0.02). Interestingly we noted a significant positive correlation of PSP/reg1A with age of the HNF1A-MODY carriers (rho = 0.40 p = 0.02) with an age of 25 years separating carriers with low and high PSP/reg1A levels. Patients with type 1 diabetes mellitus also had elevated serum levels of PSP/reg1A compared to controls, however this was independent of the duration of diabetes. CONCLUSION: Our data suggest that beta cell apoptosis contributes increasingly to the pathophysiology of HNF1A-MODY in patients 25 years and over. PSP/reg1A may be developed as a serum marker to detect increased beta-cell apoptosis, or its therapeutic response.